Legal Protection for Health Workers Towards the Implementation of Government Regulation No. 33 of 2012 concerning Exclusive Breastfeeding on Infants with Post Sectio Caesarea Mothers - Marni Siregar; Hetty W.A. Panggabean (Babali Health, 2021)
Introduction: Articles 6 and 7 of Government Regulation No. 33 of 2012 on Exclusive Breastfeeding stated that every mother who gives birth must give exclusive breast milk to the newborn, unless there is a medical indication, the mother is not present or the mother is separated from the baby. The purpose of this study was to determine the legal protection for health workers towards the implementation of government regulation concerning exclusive breastfeeding on infants with Post Sectio Caesarea mothers. Methods: This research method is empirical juridical research (field research). The author uses a statutory approach in accordance with the studied legal materials, analyzed qualitatively. The sample in this study is all 2 ObsGyn, 2 pediatrician, 9 midwives, 1 breast milk counselor, 60 post SC mothers and 60 newborns at RSUD Tarutung, RSUD Porsea, and RSUD Doloksanggul when researchers conducted research. Results: Exclusive Breastfeeding is a government program and has been outlined in Government Regulation No. 33 of 2014 on Exclusive Breastfeeding. The government is actually aggressively promoting exclusive breastfeeding through seminars, workshops and advertisements in print, electronic and social media. But this does not make exclusive breastfeeding successful as expected. The number of obstacles both external factors and internal factors of the mother. Especially on the mother of the Post Sectio Caesarea. Conclusion: Implementation of Government Regulation No.33 of 2012 on Exclusive Breastfeeding of Post Sectio Caesarea Mothers in hospitals has still not been realized.